Keanekaragaman Jenis Serangga di Taman Singha Merjosari Kota Malang: - - Alfa Safitri; Fitriya Nur Rizky; Ihda Maf’ulatul Husna; Ivandra Bagus Pranata; Moh. Arif Nur Hidayatullah; Muhammad Rizal Maulana; Indra Fardhani (Postgraduate, University of Mataram, 2023)
Insects are a group of living things that have the highest number of species. This study examines the diversity of insect species that aims to determine the diversity of insect species found in Singha Merjosari Park, Malang City. This research was conducted on Monday, November 7, 2022. This research used the observation method to collect data by direct observation. This method is used as an observation of the object of research, especially on the focus of the problem under study. The data obtained consisted of the number of species and body morphological characteristics of the insect species. The results of the study found six species of insects with different body morphologies. The special feature of insects is their body is divided into three main parts, namely the head (Caput), chest (Thorax) and stomach (Abdomen). Insects have a function to help pollinate or fertilize flowers, as decomposers or decomposers, as environmental bioindicators, as producers of materials that have high economic value such as producing honey, medicinal ingredients, as cleaners and soil conditioners so that they can be found in their distribution in the area around Singha Merjosari Park, Malang City. Â